The Effect of Environmental Color on Simple Reaction Time to Auditory Stimulus - Ehsan Khajoei Ravari; Ahmad Farokhi; Amir Abas Gholi; Nafiseh Karshenas Najaf Abadi; Saeed Soheilipour (University of Tehran, 2013)
Colors influence mood and mental state of human beings and since manis constantly in touch with colors, great important will be attached to thecolors. Exercise is also associated with different colors and is performed inan environment full of different colors. Also, one of the important factorsaffecting athletes' success is response to the stimulus. Considering theimportance of color and reaction time, this study examined the effect ofenvironmental color on simple reaction time to call in athletes. Thestatistical population consisted of male students (mean age 22.2 yr) ofUniversity of Tehran and 50 subjects were selected by the simple randomsampling method. Simple reaction time to auditory stimulus was recordedusing YB-1000 set. Analysis of variance with repeated measures andBonferroni post hoc test were used to analyze data. Findings showed thatthe smallest standard deviation and mean of simple reaction time to soundwas related to blue environment and there was a significant difference inthe reaction time between the blue environment and all environments exceptfor the white (p<0.05 ). The present results showed that exposure to blueenvironment can increase the speed of auditory information processing ininformation processing system of human beings.